2017
DOI: 10.1213/ane.0000000000001704
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Impairs Motor Function Recovery by Increasing Neuroapoptosis and Degeneration During Spinal Ischemia–Reperfusion Injury in Rats

Abstract: Our results demonstrate that the administration of inhaled isoflurane in spinal cord ischemia-reperfusion injury impairs the recovery of motor function. This response is associated with the neuronal apoptosis and degeneration. This study highlights the potential adverse effect of isoflurane on the functional recovery of ischemic spinal cord during major aortic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Isoflurane is a traditional anesthetic. Previous study has revealed that the application of isoflurane aggravates apoptosis and leads to damage in the central nervous system during cerebral ischemia‐reperfusion injury process in rats (Fang et al., 2017). Moreover, isoflurane is also known to induce damage in neuronal cells by activating the expression of p‐NF‐κB (Schallner et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane is a traditional anesthetic. Previous study has revealed that the application of isoflurane aggravates apoptosis and leads to damage in the central nervous system during cerebral ischemia‐reperfusion injury process in rats (Fang et al., 2017). Moreover, isoflurane is also known to induce damage in neuronal cells by activating the expression of p‐NF‐κB (Schallner et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The SCI mouse model was established as previously described (Le Corre et al, ). Isoflurane (1.5% v/v in oxygen) was delivered to the animals via a costume‐built oronasal mask (Fang et al, ). Laminectomy at the T11–13 level was conducted to expose the spinal cord.…”
Section: Methodsmentioning
confidence: 99%
“…In neuronal injury or neurodegenerative disease, both neuroprotective and neurotoxic effects of isoflurane are discussed [45,49]. Recently, Fang et al described an in vivo rat model of lumbar spinal cord ischemia (SCI) by cross-clamping of the thoracic aorta at the level of T5 [72]. Ischemia was performed for 25 min, followed by cord reperfusion for up to 48 h. Isoflurane 1.5 vol% was applied via inhalation perioperatively.…”
Section: The Role Of Anesthetic Agents On Ho-1 Modulationmentioning
confidence: 99%
“…SCI-induced HO-1 protein expression was further induced by isoflurane. This increase was interpreted as an enhanced inflammatory response [72].…”
Section: The Role Of Anesthetic Agents On Ho-1 Modulationmentioning
confidence: 99%